Dielectric anisotropy and dielectric relaxation dynamics in chiral and non-chiral salicylaldimine - nematic crystal composites - Canli, N. Yilmaz; Yasa, Oe; Yorur, C.; Eran, B. Bilgin; Yakuphanoglu, F. (NATL INST OPTOELECTRONICS, 2010)
The dielectric anisotropy and dielectric relaxation dynamics in 4-cyano-4'-pentylbiphenyl and salicylaldimine compounds 5-octyloxy-2-[(4-hexyloxyphenylimino)methyl]phenol (LC1) and (S)-5-octyloxy-2[{4-(2-methylbutoxy)phenylimino}methyl]phenol (LC2) composites have been investigated. The polarizing microscopy and differential scanning calorimetry results show that salicylaldimine compounds LC1 and LC2 exhibits enantiotropic SmC and SmC* mesophases, respectively. The dielectrical anisotropy of 5CB, 5CB/LC1 and 5CB/LC2 liquid crystals changes from the positive dielectric anisotropy to negative with the frequency of the applied voltage. The critical frequency f(c) values of dielectrical anisotropy for 4-cyano-4'-pentylbiphenyl and salicylaldimine compounds LC1 and LC2 liquid crystal composites were found to be 693.84, 573.77 and 562.41 kHz, respectively. The dielectric relaxation mechanism of the liquid crystals was analyzed using Cole-Cole plots and the dielectric relaxation mechanism is a non-Debye type relaxation behavior.
Keywords: Liquid crystal; Dielectric anisotropy; Salicylaldimine; Materials Science; Optics